An approach to Pueblo-Continente (1939): the construction of Latin America as a conceptual persona - Luján Sandoval, Sergio (2022)
The present study proposes an analysis of Antenor Orrego’s book Pueblo-Continente (1939) in order to prove that Latin America is built as a conceptual persona. For that purpose, we will explore the theoretical principles of Stefano Arduini, Gilles Deleuze and Felix Guattari; likewise, after reviewing the context and the critical reception of Orrego’s text, we will focus on three cardinal aspects based on Latin America: one, the presence of biological and cognitive features; two, the search for their own voice and thinking regarding Europe; and three, their sense in terms of the territory that host the new american man. Finally, we maintain that Latin America is personified in Pueblo-Continente to expose their issues and tensional processes, but also their potential as an organic and under construction scenography.